MANAGEMENT OF TEMPOROMANDIBULAR JOINT ANKYLOSIS BY INTERPOSITIONAL ARTHROPLASTY USING TEMPORALIS MUSCLE FLAP: Temporomandibular Joint Ankylosis - Afzal, Muhammad; Ibrahim, Muhammad Wasim; Qazi, Shahid Shuja (Pakistan Armed Forces Medical Journal, 2008)
.